Be Productive During the COVID-19 Pandemic at Siantar Estate - Purba, Switamy A.; Sinaga, Christa Vonni R.; Sirait, Debora E.; Sinaga, Lolyta D.; Sinaga, Rani F. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has not only hit China but almost the entire population of the world. Many of the impacts caused by this pandemic are health, economic and social problems. During the pandemic, many activities are carried out at home. Not infrequently also found many workers who were laid off or even laid off. The service carried out to the Siantar estate community is in terms of socializing how to respond to this pandemic. In this case, the community is invited to be productive during this pandemic because in addition to avoiding stress, it can also increase income for the community. This service is carried out by demonstrating the manufacture of hand washing soap and hand sanitizer, the results of which are also distributed to the Siantar Estate community.